Pendekatan Rational Emotive Behavior Therapy dalam Konseling Kelompok - Siftia Rusydi, Wasilatur Rahmah; Farid Ilhamuddin, Muhammad; Nikmatus Saniah, Farah; Ayu Arisona, Tria Putri (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Every individuals, especially students, certainly has problems in their life. Various problems are also caused by various factors, one of which is problems related to the individual’s own thingking errors which result in irrational belief (illogical). This has been researched by the character Ellis the REBT (Rational Emotive Behavior Therapy) approach which that the consequences/impact of problems faced by individuals are due to their irrational beliefs which distrub the individual themselves. Therefore, counseling is needes to help with these problems, one of which is group counseling which utilizes group dynamics. The purpose of this writing is to learn together about group counseling using the REBT approach. The method used is a literature study which examine exisiting literature. So the result can be seen that you can use group counseling with the REBT approach to help overcome problems related to irrational belief that are changed to more rational (logical). Thus, it can be concluded that overcoming the problems of irrational belief becoming rational belief from the REBT approach can be done through group counseling by utilizing group dynamics to work together to overcome these problems Keywords: REBT; Group counseling